Urinary calcium indices in primary hyperparathyroidism (PHPT) and familial hypocalciuric hypercalcaemia (FHH): which test performs best?. Issue 1151 (5th September 2020) - Arshad, Muhammad Fahad; McAllister, James; Merchant, Azhar; Rab, Edmund; Cook, Jacqueline; Eastell, Richard; Balasubramanian, Sabapathy
ABSTRACT: Aim: Primary hyperparathyroidism (PHPT) is much more common than familial hypocalciuric hypercalcaemia (FHH), but there is considerable overlap in biochemical features. Urine calcium indices help with the differential diagnosis, but their reliability in making this distinction is not clear. The aim of this study was to compare urinary calcium values in patients with PHPT and FHH. Methods: This was a case–control study of patients with PHPT who had successful surgery and genetically proven FHH between 2011 and 2016. Due to low FHH numbers, patients from neighbouring hospitals and outside study period (2017–2019) were allowed to improve power. Data on demographics and urinary calcium were obtained from electronic records and compared between the two groups. Results: During the study period, 250 patients underwent successful PHPT surgery, while in the FHH arm, 19 genetically proven cases were included. The median (IQR) 24-hour urine calcium excretion (UCE) in the PHPT group was 8.3 (5.6–11.2) mmol/24 hours compared with 3.2 (2.1–6.1) mmol/24 hour in the FHH group (p<0.001). Median (IQR) calcium to creatinine clearance ratio (CCCR) in the PHPT and FHH groups was 0.020 (0.013–0.026) and 0.01 (0.002–0.02), respectively (p=0.001). The sensitivity of urinary tests for PHPT was 96% for UCE (cut-off ≥2.5 mmol/24 hour) and 47% for CCCR (cut-off >0.02). The specificity of the urinary tests for FHH was 29.4% for UCE (cut-off <2.5 mmol/24 hour) and 93% for CCCR (cut-off <0.02). Conclusions: 24-hour UCE is more sensitive in diagnosing PHPT; however, it is less specific in ruling out FHH as compared with CCCR, when the cut-offs suggested by the International guidelines from the fourth international workshop are used. A significant proportion of patients with PHPT would have also required genetic studies if the guidelines were followed.